2017
DOI: 10.3389/fmicb.2017.01004
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Bile Salt Hydrolase from Lactobacillus gasseri FR4 and Demonstration of Its Substrate Specificity and Inhibitory Mechanism Using Molecular Docking Analysis

Abstract: Probiotic bacteria are beneficial to the health of poultry animals, thus are used as alternative candidates for antibiotics used as growth promoters (AGPs). However, they also reduce the body weight gain due to innate bile salt hydrolase (BSH) activity. Hence, the addition of a suitable BSH inhibitor along with the probiotic feed can decrease the BSH activity. In this study, a BSH gene (981 bp) encoding 326-amino acids was identified from the genome of Lactobacillus gasseri FR4 (LgBSH). The LgBSH-encoding gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 41 publications
2
50
0
Order By: Relevance
“…Another urgent question is which bile acid(s) are involved in L. gasseri-induced FXR inhibition? L. gasseri preferentially deconjugates glyco-conjugated bile acids rather than tauro-conjugated bile acids (Rani et al, 2017), which would lead to a drop in glyco-conjugated bile acid with a relatively stable level of tauroconjugated bile acids. On one hand, deconjugation of glycoconjugated bile acids would result in increased excretion of these bile acids, as deconjugation increases the hydrophobicity of bile acids leading to increased excretion (Choi et al, 2015;Schiff et al, 1972).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another urgent question is which bile acid(s) are involved in L. gasseri-induced FXR inhibition? L. gasseri preferentially deconjugates glyco-conjugated bile acids rather than tauro-conjugated bile acids (Rani et al, 2017), which would lead to a drop in glyco-conjugated bile acid with a relatively stable level of tauroconjugated bile acids. On one hand, deconjugation of glycoconjugated bile acids would result in increased excretion of these bile acids, as deconjugation increases the hydrophobicity of bile acids leading to increased excretion (Choi et al, 2015;Schiff et al, 1972).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the increase in upper small intestinal L. gasseri could restore glucoregulatory fatty acid-sensing pathways and improve glucose control in these HFD transplanted rats. L. gasseri exhibits bile salt hydrolase activity (Rani et al, 2017), and administration of L. gasseri probiotics alters the bile acid pool and promotes bile acid excretion in rats (Usman and Hosono, 2001). In parallel, the bile acid sequestrant colesevelam improves glycemic control in diabetic humans (Beysen et al, 2012;Marina et al, 2012) and rodents (Prawitt et al, 2011;Trabelsi et al, 2015) and inhibits intestinal FXR in rodents (Prawitt et al, 2011;Trabelsi et al, 2015).…”
Section: Upper Small Intestinal Microbiota Transplantation From Rc-fementioning
confidence: 99%
“…Being located at the bottom of the binding pocket, Ile56 and Leu63 may determine the differing substrate preferences of LsB‐30514_BSH1. According to the results of molecular docking studies, Cys2 and Lys59 in the substrate‐binding pocket of LgFR4_BSH are found to form hydrogen bonds with GCA . Similarly, GDCA forms hydrogen‐bonding interactions with Cys2, Phe25, and Lys59, but Lys59 and Gln135 interact with TCA via hydrogen bonding.…”
Section: Structural Basis For the Substrate Preference Of Bshsmentioning
confidence: 99%
“…When used at high concentrations, they can improve the growth performance and feed efficiency in swine and poultry . Some currently used AGPs such as penicillin V, ampicillin, doxycycline hydrochloride, and tetracycline also show significant inhibitory effects on BSH activities. However, long‐term use of these metal ions and antibiotics affects animal health, and increases the accumulation of metal ions in the treated animals and the environment as well as the risk of acquiring antibiotic‐resistant bacteria, respectively.…”
Section: Bsh Inhibitor Developmentmentioning
confidence: 99%
“…Recently, several studies have been published on the distribution and activity of BSH in more than 300 lactic acid bacteria strains from the genera Bifidobacterium and Lactobacillus, and the species Lactococcus lactis, Leuconostoc mesenteroides, and Streptococcus thermophilus (González-Vázquez et al 2015;Xu et al 2016;Rani et al 2017). Lactobacillus spp.…”
Section: Introductionmentioning
confidence: 99%